Small-signal analysis of a single-stage bridgeless boost half-bridge AC/DC converter with bidirectional switch - Mohamad Affan Bin Mohd Noh; Mohd Rodhi Bin Sahid; Thang Ka Fei; Ravi Lakshmanan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
A small-signal analysis of a single-stage bridgeless boost half-bridge alternating current/direct current (AC/DC) Converter with bidirectional switches is performed using circuit averaging method. The comprehensive approach to develop the small signal model from the steady state analysis is discussed. The small-signal model is then simulated with MATLAB Simulink. The small-signal model is verified through the comparison of the bode-plot obtained from MATLAB Simulink and the simulated large signal model in piecewise linear electrical circuit simulation (PLECS). The mathematical model obtain from the small-signal analysis is then used to determine the proportional gain K_p and integral gain K_i. In addition, the switch large-signal model is developed by considering the current and voltage waveforms during load transients and steady-state conditions.